1996
DOI: 10.1121/1.414809
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in anisotropic, saturated porous media: Plane-wave theory and numerical simulation

Abstract: Porous media are anisotropic due to bedding, compaction, and the presence of aligned microcracks and fractures. Here, it is assumed that the skeleton (and not the solid itself) is anisotropic. The rheological model also includes anisotropic tortuosity and permeability. The poroelastic equations are based on a transversely isotropic extension of Biot’s theory, and the problem is of plane strain type, i.e., two dimensional, describing qP−qS propagation. In the high-frequency case, the (two) viscodynamic operator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
119
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 0 publications
3
119
1
Order By: Relevance
“…Suppose we have values of K(ω j ) = K(is j ) = P (s j ) for different nonzero real-valued frequencies ω 1 , ω 2 , · · · , ω M , then we can generate another M -interpolation points by using the symmetry of (19) …”
Section: Formulation and Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose we have values of K(ω j ) = K(is j ) = P (s j ) for different nonzero real-valued frequencies ω 1 , ω 2 , · · · , ω M , then we can generate another M -interpolation points by using the symmetry of (19) …”
Section: Formulation and Algorithmmentioning
confidence: 99%
“…There have been a few papers which proposed different methods for handling the memory terms. Among them, the most popular ones are the fractional derivative approach for Biot-JKD model, which requires complicated quadrature rules [47] and the phenomenological one which proposed to approximates the memory terms with sums of exponential decay kernels [64], [19]. The latter is more computationally efficient but it is not clear how the weights and decay rates of the exponential decay kernels can be found in a systematic way.…”
Section: Introductionmentioning
confidence: 99%
“…Attenborough et al [29] presented tortuosities deduced from audio-frequency measurements in air-filled cancellous bone replicas and showed that there was strong anisotropy. The Biot theory has been further developed including semi-analytical approach that allows for transverse anisotropy in the frame elastic moduli, tortuosity and permeability for geophysical applications [30]. A modified Biot-Attenborough (MBA) model has also been proposed for acoustic wave propagation in a non-rigid porous medium with circular cylindrical pores starting from a formulation for a rigid-framed porous material [31]- [33].…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Biot (1956), many authors (de la Cruz and Spanos, 1985;Johnson et al, 1994;Geerits and Kedler, 1997) have contributed to improve the poro-elastodynamic equations, either by averaging or by integrating techniques. The forward problem, i.e., the computation of synthetic seismograms in poro-elastic media has been developed and solved with several techniques (Dai et al, 1995;Carcione, 1996;Haartsen and Pride, 1997;Garambois and Dietrich, 2002). The model involves more parameters than the elastic case, but on the other hand, the wave velocities, attenuation and dispersion characteristics are computed from the medium's intrinsic properties without resorting to empirical relationships.…”
Section: Introductionmentioning
confidence: 99%